Aggressive lung donor management increases graft procurement without increasing renal graft loss after transplantation. (16th August 2012) - Miñambres, Eduardo; Ballesteros, Maria A.; Rodrigo, Emilio; García‐Miguélez, Ana; Llorca, Javier; Ruiz, Juan C.; Arias, Manuel
Abstract Background To determine the impact of an aggressive protocol on the rate of lung grafts available for transplant. We analyzed the impact of this management on kidney graft survival after kidney transplantation. Methods A cohort study. Lung donors and kidney recipients from 2009 and 2010 were considered the prospective cohort with 2003–2008 as the historical control period. The number of lungs available for transplantation was the main outcome measures. For recipients, kidney graft survival was the main outcome measure. Results We quadrupled the number of lung donors in the period 2009–2010 compared with the historical control. Management in the prospective cohort included higher use of positive end‐expiratory pressure (PEEP) (p < 0.0001), increased use of hormonal resuscitation therapy (HRT) (p < 0.0001), and lower level of central venous pressure (p < 0.05) than historical control. The probability of renal graft survival at one yr after transplant was 88.6% (CI 95%: 74.8–95.1) in historical control and 94.7% (CI 95%: 81–98.7%) in the prospective cohort (p = 0.226). Conclusions Aggressive management strategy in potential lung donors, which includes ventilator recruitment maneuvers, PEEP ≥8 cm H2O, the use of HRT, and restrictive fluid balance increases the rate of lung grafts available for transplantation without adverse effect on kidney graft survival.